Challenges in gluten‐free diet in coeliac disease: Prague consensus. (19th April 2017) - Samasca, Gabriel; Lerner, Aaron; Girbovan, Anamaria; Sur, Genel; Lupan, Iulia; Makovicky, Peter; Matthias, Torsten; Freeman, Hugh J.
Abstract: Background: New treatments in coeliac disease are being vigorously pursued to either replace or facilitate the difficult‐tofollow gluten‐free diet. Design: The present review intends to summarise the challenges in gluten‐free diet adherence during the transitional period, as reflected in the last Prague consensus, published in 2016. Results: The honourable panel members recommended that dietary adherence and the consequences of nonadherence represent key components for discussion in the transitional period setting. Conclusions: There are numerous difficulties in adhering to gluten withdrawal, but the transition period from adolescence to young adulthood is considered a fragile and high‐risk period for intentional and unintentional gluten intake.